The Manifestations and Consequences of Job Burnout among Academic Leaders in Saudi Arabia: A Qualitative Study - Alsulami, Agel Fara (Journal of Posthumanism, 2025)
This qualitative study aimed to identify how job burnout manifests among academic leaders in Saudi universities, as well as its consequences. It addresses a gap in the literature by exploring how burnout manifests at personal, social, and institutional levels in this setting. Using the Job Demands-Resources (JD-R) theory and Maslach’s burnout model (emotional exhaustion, depersonalisation and reduced accomplishment) as a theoretical framework, the study conducted in-depth interviews with 25 academic leaders from five public state universities. Respondents participated in semi-structured interviews (2–2.5 hours long), delivered face-to-face or by telephone. Thematic analysis revealed the challenges and impacts of burnout: work–life integration challenges, cultural pressures, and lack of support. These findings provide useful information for targeted interventions to reduce the impact of burnout and promote well-being in Saudi Arabian higher education settings.